(untitled) (Research, Society and Development, 2022)
Introduction: The advances in medical technology play a significant role in the acquisition of knowledge and skills by healthcare professionals. Objective: The objective of this study was to apply and analyze the usability of the mammographic teaching software (RADIF) as a didactic tool for Radiologic Technology students. Materials and methods: This exploratory and descriptive study with a quantitative approach, was carried out in partnership with research groups from the Federal Institute of Education, Science, and Technology of Santa Catarina (IFSC) and the Federal Institute of Education, Science and Technology of Bahia (IFBA). The sample size was 31 Radiologic Technology students. Results: The sample obtained 85% of correct answers to all questions, the highest percentage of correct answers was in the modules on radiological breast anatomy, positioning techniques, and mammographic views. The highest error rate 61.2%, was related to the radiological aspects area. The sample showed a positive evaluation of more than 95% regarding the use of the software criteria. Conclusion: The results indicated a positive view regarding the use and applicability of the RADIF software for teaching and training in the radiological anatomy of the breast.